Investigation of transcriptome changes during flower development using third-generation sequencing and inducible gene perturbation approaches - Finocchio, Andrea (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Genetics, 2023)
Over the last 30 years, flower development has been intensively studied us- ing a wide range of genetic and molecular methods. Much of this work was guided by the ABC model of floral organ identity specification, which posits that a small number of regulatory genes, termed the floral homeotic genes, act in a combinatorial manner to specify the four different types of floral organs. Although the central tenets of this model have been confirmed in diverse angiosperms, the molecular activities of the transcription factors that are encoded by the floral homeotic genes are not well understood and there are layers of regulation that are still largely unexplored. The development of methods, including new sequencing approaches that move past the mea- surement of gene expression, and instead shift the focus deeper, to the level of single transcripts or cells, holds the potential for further progress in our understanding of flower development. At the same time, there is now a focus on the application of the knowledge already gained to improve crop plants and to generate new varieties with improved traits. These new varieties are urgently needed as they could aid in alleviating the effects of climate change on crop production and to make agriculture more sustainable. Based on dis- coveries made in our laboratory, we are currently exploring the potential of trichomes, or hairs, for the protection of crops against insect pests. Specifi- cally, we are attempting to induce trichomes on seed pods of Brassica crops to make them more resistant to herbivory. To underpin this translational research and to broaden the knowledge base for the processes under study, my work aimed at investigating the processes of flower development and trichome formation in more detail. To this end, I conducted three largely separate projects using the model plant Arabidopsis thaliana: in the first project (Chapter 3), I used cutting-edge long-read direct cDNA sequencing with the Oxford Nanopore MinION to build a new atlas of the Arabidopsis transcriptome during flower development, to improve our understanding of complex transcriptome dynamics, and to generate a valuable reference dataset for the scientific community for use in future studies. In the second project (Chapter 4), I studied two key trichome repressors, TRIPTYCHON (TRY) and CAPRICE (CPC) because it has been shown that their inactiva- tion can lead to the formation of trichomes on carpel valves and are a major target for the ongoing translational research in our laboratory. Specifically, I explore the interactome around TRY and CPC using TurboID, a recently developed proximity labeling system, as well as immunoprecipitation coupled with mass spectrometry. Work in the third project (Chapter 5), was cen- tered around the floral homeotic factors APETALA3 (AP3) and AGAMOUS (AG), which are involved in the specification of floral organ identities. Using an inducible gene perturbation approach combined with RNA-sequencing, I explored the gene expression programs acting downstream of these master regulators at different stages of early flower development.
APPROVED
Keywords: Plant Genetics; Flower development